1994
DOI: 10.1021/bi00251a001
|View full text |Cite
|
Sign up to set email alerts
|

Thiol ester-linked p-coumaric acid as a new photoactive prosthetic group in a protein with rhodopsin-like photochemistry

Abstract: Dux, P.; Hard, K.; Devreese, B.; Nugteren-Roodzand, I.M.; Crielaard, W.; Boelens, R.; Beeumen, J.; Kaptein, R.; Hellingwerf, K.J. Published in: Biochemistry DOI:10.1021/bi00251a001Link to publication Citation for published version (APA):Hoff, W. D., Dux, P., Hard, K., Devreese, B., Nugteren-Roodzand, I. M., Crielaard, W., ... Hellingwerf, K. J. (1994). p-Coumaric acid, a new photoactive chromophore of a yellow photoreceptor protein with rhodopsin-like characteristics. Biochemistry, 33, 13959-13963. DOI: 10.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
274
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(283 citation statements)
references
References 18 publications
9
274
0
Order By: Relevance
“…By absorbance of a photon, PYP is excited into a photocycle that involves a red-shifted and a blue-shifted intermediate (Meyer et al, 1987;Hoff et al, 1994c), very similar to what has been described for the sensory rhodopsins (Spudich & Bogomolni, 1988). However, we have recently determined the PYP cofactor to be a p-coumaric acid molecule [Hoff et al, 1994a;confirmed in Baca et al (1994)] linked to Cys 69 [see Van Beeumen et al (1993)], presumably via a thiol ester bond. Therefore, it is very different from the Schiff base-bound retinal molecule present in the rhodopsins.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…By absorbance of a photon, PYP is excited into a photocycle that involves a red-shifted and a blue-shifted intermediate (Meyer et al, 1987;Hoff et al, 1994c), very similar to what has been described for the sensory rhodopsins (Spudich & Bogomolni, 1988). However, we have recently determined the PYP cofactor to be a p-coumaric acid molecule [Hoff et al, 1994a;confirmed in Baca et al (1994)] linked to Cys 69 [see Van Beeumen et al (1993)], presumably via a thiol ester bond. Therefore, it is very different from the Schiff base-bound retinal molecule present in the rhodopsins.…”
supporting
confidence: 79%
“…This experiment was repeated using 11 mg of pure PYP. NMR measurements of the resulting chromophore-containing fraction in D 2 O indicated that in this procedure the bond between the chromophore and the apoprotein was broken [ Table 1; see Hoff et al (1994a)], explaining the difference in absorption spectra between this fraction and the pepsin-generated chromopeptide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ground state pG, the chromophore of PYP is in the trans configuration (referring to the vinyl protons) and in the deprotonated state (the p-hydroxy group), as was indicated by 1H NMR [1] and resonance Raman spectroscopy [12], respectively. It has been proposed that also in the case of PYP lightinduced chromophore photo-isomerization occurs [1,28].…”
Section: Introductionmentioning
confidence: 91%
“…Photoactive yellow protein (PYP) from the purple sulfur bacterium Ectothiorhodospira halophila is the first eubacteriai photoreceptor to be characterized in detail and has recently been shown to contain a new chromophoric group: thiol ester linked p-coumaric acid [1,2]. This is t he first report of a physiological role for p-coumaric acid in rrokaryotes, a compound previously identified in higher plants, where it plays a central.…”
Section: Introductionmentioning
confidence: 99%